2015
DOI: 10.1590/0034-737x201562050012
|View full text |Cite
|
Sign up to set email alerts
|

Uso de biofertilizante na produção de mudas de repolho

Abstract: A utilização de produtos biofertilizantes, como fermentados bacterianos, contendo aminoácidos, é pouco estudada na produção de mudas de hortaliças, especialmente no sistema orgânico. Neste trabalho, o objetivo foi avaliar o efeito da aplicação foliar de um fermentado bacteriano do melaço da cana, contendo 30% do aminoácido ácido Lglutâmico, no desenvolvimento de mudas de repolho. Os tratamentos, constituídos por quatro repetições, eram compostos por concentrações do fermentado (0; 0,1; 0,2; 0,4 e 0,8 mL L -1 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
2
6
0
2
Order By: Relevance
“…Application of 0.2 mL.L -1 AG30 increased leaf area by 47% compared to the control (Figure 4). Röder et al (2015) found similar results using bacterial fermented containing L-glutamic acid in cabbage seedlings. However, at a higher concentration (0.8 mL.L -1 ), leaf area increased by 22% compared to the control with no application.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…Application of 0.2 mL.L -1 AG30 increased leaf area by 47% compared to the control (Figure 4). Röder et al (2015) found similar results using bacterial fermented containing L-glutamic acid in cabbage seedlings. However, at a higher concentration (0.8 mL.L -1 ), leaf area increased by 22% compared to the control with no application.…”
Section: Resultssupporting
confidence: 61%
“…However, a significant gain was observed in the relative chlorophyll index compared to the control in seedlings of Brassica oleracea var. capitata submitted to the application of bacterial fermented containing L-glutamic acid (Röder et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the leaves expansion could be a consequence of the stimulus to chlorophyll synthesis, photosynthesis, and increase on sugar content, with all of these pathways related to the AA metabolism on plants [40]. The increase on Chl by AA application was previously reported regarding to the biosynthesis of aminolevulinic acid from the intact carbon skeleton of exogenously applied L-glutamic acid [41], and the joint increases of Chl, AA and plant growth by AA application, were also found by use of fermentation based biofertilizer containing 29% (w/v) of free AA applied on cabbage seedlings [42]. Figure 3(a), Figure 3(b) and Figure 3(d), express the Apb remarkable eliciting effect on Chl, AA and protein biosynthesis, that are connected to the plant growth promotion (Figure 2).…”
Section: Resultssupporting
confidence: 52%